Analisis Collaborative Governance dalam Mendukung Pariwisata Berkelanjutan di Kawasan Bunaken National Park Kota Manado - Jericho Danga Pombengi; Joyce Jacinta Rares; Ghiska Marunsenge; Gychella Aurelia Maidangkay; Meiny Elizabeth Sumampouw; Chesika Aurelia Roring (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2026)
This study aims to analyze the implementation of collaborative governance in supporting sustainable tourism in the Bunaken National Park area, Manado City. Tourism development in this region has significant economic potential, yet its management still faces challenges related to coordination among stakeholders. Theoretically, the success of collaboration is influenced by starting conditions, trust building, power balance, and commitment to process (Ansell & Gash, 2008). This research employs a qualitative method with a case study approach. Data were collected through in-depth interviews, field observations, and documentation involving government agencies, local communities, and tourism business actors. The findings reveal that the implementation of collaborative governance has not been optimal. Weak initial conditions, low levels of trust, imbalanced power relations, and inconsistent commitment among stakeholders have hindered effective collaboration. These challenges result in poor coordination, limited participation, and underdeveloped institutional capacity in tourism management. In addition, issues related to accessibility, facilities, and institutional arrangements further affect the sustainability of the destination. Therefore, strengthening collaborative governance is essential through improving coordination mechanisms, enhancing transparency, ensuring balanced stakeholder participation, and reinforcing long-term commitment. This study contributes to the understanding of governance practices in sustainable tourism and offers practical recommendations for improving stakeholder collaboration in managing conservation-based tourism areas.